Pelatihan dan Pendampingan Siswa dalam Pembuatan Database Produk Menggunakan Microsoft Access di SMK Abdi Karya Bekasi: Training and Mentoring Students in Creating Product Databases Using Microsoft Access at SMK Abdi Karya Bekasi - Noviana, Rina; Winarti, Winarti; Indriani, Devi; Andryani, Dewi; Ramadha, Kartika Nur; Rasal, Isram; Utomo, Joko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Community service activities are one form of realizing the tri dharma of higher education which aims to contribute by going directly into the field to help the community or school in several activities. SMK Abdi Karya is a vocational school that collaborates with the Gunadarma University Community Service Team (Abdimas). The Abdimas team consists of 7 lecturers. The problem partners face is that there is no data management on student work products at SMK Abdi Karya. Products made by students include key chains, recycled bags, digital products, and handicraft products, which have not yet been managed into product data stored in a database. Students are not yet able to utilize Microsoft Access as an application that can process and store various types of data. In office automation lessons using Microsoft Access, only theory is given without direct practice. This community service activity aims to provide training and practical assistance to students in managing product data using Microsoft Access. Students are given training in creating databases and storage tables, how to manage product data, and create reports. The community service activity program includes the preparation of learning materials, training, and evaluation of activities. The results of community service activities are in the form of learning modules, product photos, and student learning evaluation results.